The Moderating Role of Ethnic Identity on the Relationship Between School Climate and Self-Esteem for African American Adolescents. Issue 3 (14th September 2020) - Fisher, Amy E.; Fisher, Sycarah; Arsenault, Chelsea; Jacob, Rachel; Barnes-Najor, Jessica
ABSTRACT: Positive self-esteem is linked to academic success for K–12 students. However, self-esteem declines during adolescence, especially for African Americans. Positive perceptions of school climate are well-studied predictors of self-esteem. Given the risk for greater declines in self-esteem experienced by African American students, this study sought to examine the moderating role of ethnic identity on the relationship between school climate and self-esteem for a sample of 1, 343 African American adolescents in the Midwest. Regression analysis using the PROCESS macro indicated that ethnic identity positively influenced the relationship between perceptions of school climate on self-esteem for African American adolescents at all levels. Implications for school interventions to foster positive adolescent ethnic development are discussed.